Nrf2 protects against oxidative stress induced by SiO2 nanoparticles. (October 2017) - Liu, Wei; Hu, Tao; Zhou, Li; Wu, Desheng; Huang, Xinfeng; Ren, Xiaohu; Lv, Yuan; Hong, Wenxu; Huang, Guanqin; Lin, Zequn; Liu, Jianjun
Aim: The aim of our study was to explore the role of nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2) on the exposure of SiO2 nanoparticles (NPs) and its influence.Materials & methods: To understand the mechanism of NP-induced oxidative stress, the involvement of oxidative-stress-responding transcription factors and the Nrf2/antioxidant reactive element (ARE) signaling pathway in the toxicity of SiO2 NPs' exposure was investigated via in vivo and in vitro models.Results: A549 cells showed a significant cytotoxic effect while A549-shNrf2 cells showed decreased cell viability after nm-SiO2 exposure. SiO2 NPs' exposure activated the Nrf2/ARE signaling pathway. Nrf2 −/− exposed mice showed increased reactive oxygen species, 8-hydroxyl deoxyguanosine level and decreased total antioxidant capacity. Nrf2/ARE signaling pathway activation disrupted, leading inhibition of heme oxygenase-1 and upregulation of PKR-like endoplasmic-reticulum-regulated kinase.Conclusion: Our findings suggested that Nrf2 could protect against oxidative stress induced by SiO2 NPs, and the Nrf2/ARE pathway might be involved in mild-to-moderate SiO2 NP-induced oxidative stress that was evident from dampened activity of Nrf2.